2023
DOI: 10.1186/s12891-023-06422-w
|View full text |Cite|
|
Sign up to set email alerts
|

Learning curve of robot-assisted total knee arthroplasty and its effects on implant position in asian patients: a prospective study

Abstract: Background Robot-assisted total knee arthroplasty (r-TKA) can reportedly achieve more accurate implant positioning than conventional total knee arthroplasty (c-TKA), although its learning curve is controversial. Moreover, few studies have investigated r-TKA in Asians, who have different anatomical characteristics. This study aimed to determine the learning curve for r-TKA and compare implant positions between r-TKA and c-TKA according to the learning curve in Asian patients. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Finally, this study included the initial cases from the learning curve of the robotic arm-assisted system. However, a previous study confirmed that the final implant positions and outliers were not significantly different between the initial cases and proficiency cases [16]. Therefore, it was determined to be reliable even though the initial cases were included.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, this study included the initial cases from the learning curve of the robotic arm-assisted system. However, a previous study confirmed that the final implant positions and outliers were not significantly different between the initial cases and proficiency cases [16]. Therefore, it was determined to be reliable even though the initial cases were included.…”
Section: Discussionmentioning
confidence: 91%
“…RTKA is known for its advantages, such as accurate implant positioning and fewer outliers. Jung et al [16] confirmed that RTKA resulted in fewer position errors in the sagittal tibial component and femoral component rotation as well as fewer outliers in the hip-knee-ankle angle, coronal femoral component position, sagittal tibial component position and femoral component rotation position. However, the relationship between accurate implant positioning and clinical outcomes remains controversial.…”
Section: Discussionmentioning
confidence: 93%
“…Omnibot (Corin, Tampa, FL, USA) does not require preoperative imaging, jigs are mounted after performing the tibial cut, and, through a laminar spreader, it was the first robot to provide soft tissue balancing estimates and adjust femoral cuts accordingly. OMNIBOT requires nine cases for the learning curve with increased surgical time of around 20 min [ 35 ]. Several TKAs have been conducted demonstrating great implant survival at six-year follow-up [ 36 ].…”
Section: Type Of Robotic Devicesmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified the following minor typographical errors in Tables 1 and 3, which are not significant regarding result.…”
mentioning
confidence: 99%